The influence of event quality on perceived value and tourist satisfaction with regional sport events - Hans Hartanto; Veny Megawati (Southeast Asian Journal of Service Management, 2025)
This study explores the relationships between event quality, destination image, perceived value, tourist satisfaction, and destination loyalty in the context of the 2019 East Java Provincial Sports Week (Porprov) event. The research aims to understand how these factors influence tourists' loyalty to a destination, with a focus on small-scale sporting events. Hypotheses were developed based on the assumption that event quality positively affects destination image, perceived value, and tourist satisfaction, which in turn influence destination loyalty. Data were collected from 170 respondents using a snowball sampling technique and analyzed using Structural Equation Modeling (SEM) with AMOS 24. The findings revealed that event quality significantly positively impacts destination image, perceived value, and tourist satisfaction. Moreover, both destination image and perceived value were found to positively influence tourist satisfaction and destination loyalty. Tourist satisfaction was identified as a crucial mediator in the relationship between destination image and perceived value with destination loyalty. These results highlight the importance of high-quality events in shaping positive perceptions of a destination and fostering long-term loyalty among tourists. The study provides practical recommendations for event organizers and destination marketers, emphasizing the need to enhance event quality and tourist satisfaction to build enduring relationships with visitors.